PENGARUH LIFE STYLE DAN TREND TERHADAP MINAT BELI MINUMAN KOPI YANG DIMEDIASI OLEH PRODUCT KNOWLEDGE (Studi Kasus Pada Pelanggan Cafe/Kedai di Kota Klaten) - hadi, abdul; Muhammad Pualam , Fadel; Nursito, Sarwono; Haris, Abdul (Kajian Ekonomi dan Bisnis, 2023)
This study aims to investigate the effect of lifestyle and trends on consumer buying interest and the role of product knowledge as a mediator in this relationship. Research uses a quantitative approach to carry out theory testing by using hypotheses and data collection to support or reject the hypothesis. The data was obtained through a survey of respondents who are consumers of coffee drinks. Data collection techniques using a questionnaire. Regression analysis and Sobel's test were used to examine the relationship and mediation between these variables. The estimated parameter value of the estimated regression weight coefficient is 0.209 and the CR value is 1.986 and the probability value is 0.047 (p0.05) this shows that the relationship between Life Style and Purchase Interest. The estimated parameter value of the estimated regression weight coefficient is 0.202 and the CR value is 2.17 and the probability value is 0.030 (p0.05) this shows that there is a trend relationship with buying interest. Based on the results of the Sobel test analysis, it was obtained that the tcount was 2.65901242 > 1.96 with a significance level of 0.047 <0.05 (5%), thus proving that Product Knowledge is a mediating variable on the effect of Life Style on Purchase Intention. Based on the results of the Sobel test analysis, it was obtained that the tcount was 2.64535735 > 1.96 with a significance level of 0.030 <0.05 (5%), thus proving that Product Knowledge is a mediating variable on the influence of Trends on Purchase Interest. Keyword : Li festyle, consumer buying interest, trend, product knowledge